2017
DOI: 10.4103/1119-3077.180071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation on the shear bond strength of self-adhesive luting cement in different preparation depths

Abstract: According to the two-way ANOVA results, depth of preparation and treatment protocol and their interactions were significant on shear bond strength of resin cement (P Conclusions: This study detected significant differences between the irradiated and nonirradiated groups, probably due to the changes in the crystalline structure of dental hard tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Some of important findings of studies indicated the influence of filler technology, coupling phenomena, aging factor, storage in different mediums etc. on the physical, mechanical, thermo-mechanical and wear performance of dental composite, Table 1 [75][76][77][78][79][80][81][82][83][84][85].…”
Section: Influence Of Filler Constituents On the Performance Of Dentamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of important findings of studies indicated the influence of filler technology, coupling phenomena, aging factor, storage in different mediums etc. on the physical, mechanical, thermo-mechanical and wear performance of dental composite, Table 1 [75][76][77][78][79][80][81][82][83][84][85].…”
Section: Influence Of Filler Constituents On the Performance Of Dentamentioning
confidence: 99%
“…Due to the changes in the crystalline structure of dental hard tissues, the depth of preparation, treatment and their interactions were significant on shear bond strength of resin cement [82]. 9 Kamalak et al, 2018 The structural stability, thermal conductivity, thermal analysis, materials' homogeneity of newly developed flowable composites were performed.…”
Section: Carreiro and Cruz 2004mentioning
confidence: 99%
“…The depth of dentin is an important factor affecting the bond strength because deeper dentin has a higher number and diameter of dentinal tubules, and therefore, the quality of resin tags would be different compared to that in the superficial dentin [ 17 , 18 ]. Therefore, to minimize the effect of this confounding factor, we tried our best to expose the mid-coronal dentin of all tested teeth for standardization.…”
Section: Discussionmentioning
confidence: 99%